Coincidence point results of nonlinear contractive mappings in partially ordered metric spaces - Kalyani,K. (Universidad de La Frontera. Departamento de Matemática y Estadística., 2021)
ABSTRACT In this paper, we proved some coincidence point results for f-nondecreasing self-mapping satisfying certain rational type contractions in the context of a metric space endowed with a partial order. Moreover, some consequences of the main result are given by involving integral type contractions in the space. Some numerical examples are illustrated to support our results. As an application, we have discussed the existence of a unique solution of integral equation.